Socialisation of Bullying Prevention for Foster Children at LKSA Budi Mulia Sumbersari-Jember - Bashori, Dhofir Catur; Putra, Dhian Wahana (Universitas Muhammadiyah Jember, 2024)
This socialisation activity on Bullying Prevention for Foster Children at LKSA Budi Mulia Sumbersari aims to equip foster children with knowledge about bullying, including the definition and scope of bullying, forms of bullying, signs of bullying, and attitudes towards bullying behaviour. This is important to do because educational institutions, dormitories, and orphanages are places where bullying behaviour thrives. The seniority factor is the dominant factor in the chain of bullying behaviour. Therefore, it is necessary to carry out this socialisation activity to break the chain of this deviant behaviour through socialisation activities. The method used in the activity is the lecture method which contains socialisation, mentoring, and campaigns in the form of signing commitments and mutual agreements to prevent bullying in the LKSA Budi Mulia environment. After this activity, it is hoped that foster children will gain knowledge about bullying so that they do not become perpetrators of bullying against fellow foster children, and know the attitudes that must be taken if they face bullying from others. In the future, it is necessary to continue to conduct massive socialisation to foster children so that they do not commit acts of bullying, and continue to provide assistance to foster children, especially for victims of bullying so that they do not experience prolonged trauma.